And wrote my story anyway : black South African women's novels as feminism - Boswell, Barbara (Wits University Press, 2021)
Part literary history, part feminist historiography, Barbara Boswell's And Wrote My Story Anyway: Black South African Women's Novels as Feminism examines ten novels and places them in a conversation with each other. The result is an arc of feminist criticism speaking forcefully to racist, white-dominated, patriarchal power.
Keywords: Women, Black -- South Africa.; Feminists -- South Africa.; Racism -- South Africa.; Feminist criticism -- South Africa.; Nationalism -- South Africa.; Women in literature.; Feminist literary criticism -- South Africa.; Femmes noires -- Afrique du Sud.; Féministes -- Afrique du Sud.; Racisme -- Afrique du Sud.; Critique féministe -- Afrique du Sud.; Nationalisme -- Afrique du Sud.; Femmes dans la littérature.; Feminist criticism; Feminists; Nationalism; Racism; Women, Black; Women in literature; South Africa